2020
DOI: 10.3389/fneur.2020.00684
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-Related Brain Network Alterations in Patients With Temporal Lobe Glioma in the Left Hemisphere

Abstract: Background: Seizures are a common symptom in patients with temporal lobe gliomas and may result in brain network alterations. However, brain network changes caused by glioma-related epilepsy (GRE) remain poorly understood. Objective: In this study, we applied graph theory analysis to delineate topological networks with resting-state functional magnetic resonance images (rs-fMRI) and investigated characteristics of functional networks in patients with GRE. Methods: Thirty patients with low-grade gliomas in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Global efficiency was significantly decreased, and the shortest path length was significantly increased in both the insL and insR groups as compared with those in the control group. These findings are consistent with the findings from previous studies 25 28 , and indicates that the pathways of information conveying change as DLGGs grow.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Global efficiency was significantly decreased, and the shortest path length was significantly increased in both the insL and insR groups as compared with those in the control group. These findings are consistent with the findings from previous studies 25 28 , and indicates that the pathways of information conveying change as DLGGs grow.…”
Section: Discussionsupporting
confidence: 92%
“…The one is that contralesional insula participated in functional network reorganizations. Since, the glioma is commonly thought to disrupt functional networks and decrease FC 25,32,33 . Hence, the increasing FC implied that network reorganization occurred similar to what other studies have shown 3,10,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…A software, Graph Theoretical Network Analysis (https://www.nitrc.org/projects/gretna), 12,13 was used to process rs‐fMRI data. The pipeline was the same as in the previous study 10 and is shown in the Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…Topological properties of the four sub‐networks were analyzed using graph theory measurement, which included global properties (the shortest path length, global efficiency, local efficiency, clustering coefficient, transitivity, and vulnerability), nodal properties (nodal efficiency, nodal local efficiency, nodal clustering coefficient, degree centrality), and small‐worldness 10,15,16 . The details of properties were shown in part 2 of the Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation